Biohybrid robotics: From the nanoscale to the macroscale. (2nd February 2021) - Mestre, Rafael; Patiño, Tania; Sánchez, Samuel
Abstract: Biohybrid robotics is a field in which biological entities are combined with artificial materials in order to obtain improved performance or features that are difficult to mimic with hand‐made materials. Three main level of integration can be envisioned depending on the complexity of the biological entity, ranging from the nanoscale to the macroscale. At the nanoscale, enzymes that catalyze biocompatible reactions can be used as power sources for self‐propelled nanoparticles of different geometries and compositions, obtaining rather interesting active matter systems that acquire importance in the biomedical field as drug delivery systems. At the microscale, single enzymes are substituted by complete cells, such as bacteria or spermatozoa, whose self‐propelling capabilities can be used to transport cargo and can also be used as drug delivery systems, for in vitro fertilization practices or for biofilm removal. Finally, at the macroscale, the combinations of millions of cells forming tissues can be used to power biorobotic devices or bioactuators by using muscle cells. Both cardiac and skeletal muscle tissue have been part of remarkable examples of untethered biorobots that can crawl or swim due to the contractions of the tissue and current developments aim at the integration of several types of tissue to obtain more realistic biomimetic devices, which could lead to the next generation of hybrid robotics. Tethered bioactuators, however, result in excellent candidates for tissue models for drug screening purposes or the study of muscle myopathies due to their three‐dimensional architecture. This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Abstract : Bio‐hybrid robotics can be studied in terms of the scale of integration of the biological and artificial components, ranging from biomolecules like enzymes to multiple cells in the form of tissues.